Music of the Minnesinger and Early Meistersinger - Linker, Robert W. (1962)
Originally published in 1962, this complete bibliography of the music of the Minnesinger provided an essential tool for scholars of medieval German literature. The songs are listed in alphabetical order by composer along with information on the manuscript and folio, ascription, and publication. A list of manuscripts organized by library as well as the chief books and articles dealing with this material is included